Cost Management as the Most Important Tool of Anti-crisis Plans - Jana KAJANOVA; Lukas VETESKA (Communications of International Proceedings, 2020)
The crisis caused by Covid in 2020 has shown how suddenly the market situation and society can change. Many managers did not expect such a sharp and rapid crisis after a decade of economic growth. Some businesses crisis has caught unprepared. The sharp decline in turnover due to government restrictive measures has caused an acute shortage of liquid assets in most companies. The company can go through a similar crisis by creating an anti-crisis plan, which describes the reactions to individual adverse market situations that may occur. This gives managers the advantage of pre-built sets of measures that they can apply immediately, making their responses more flexible. The most important and most used tool is cost reduction. When identifying possible savings, cost controlling is important, which gives us important information about the cost structure in the company. Modern cost management methods such as ABC identify activities in the company that can be limited or eliminated altogether.
Keywords: Cost Controlling; Anti-Crisis Plan; Cost Management.